Mediastinoscope-controlled parasternal fenestration of the pericardium: definitive surgical palliation of malignant pericardial effusion - Toth Imre; Szucs Geza; Molnar Tamas F (Journal of Cardiothoracic Surgery, 2012)
Abstract Background The tumorous infiltration or carcinosis of the pericardium could cause pericardial effusion in up to one-third of cases of malignancy, thus potentially interfere with the otherwise desirable oncological treatment. The existing surgical methods for the management of pericardial fluid are well-established but are not without limitations in the symptomatic relief of malignant pericardial effusion (MPE). The recurrence rate ranges between 43 and 69% after pericardiocentesis and 9 to 16% after pericardial drainage. The desire to overcome relative limitations of the existing methods led us to explore an alternative approach. Methods The standard armamentarium of the Carlens collar mediastinoscopy procedure was utilized in a Chamberlain parasternal approach of the pericardial sac. The laterality of approach was decided based upon the pleural involvement, as tumor-free pericardiopleural reflection is required. A pericardio-pleural window at least 3 cm in diameter was created. From January 2000 to December 2009, 22 cases were operated on with mediastinoscope-controlled parasternal fenestration (MCPF). Considering the type of the primary tumor, there were 11 lung cancer, 6 breast cancers, 2 haematologic malignancies and in 3 patients the origin of malignancy could not be verified. Results There were no operative deaths. We lost one patient (4.5%) in the postoperative hospital period. All of the surviving patients had a minimum of 2 months of symptom-free survival. We detected transient recurrence of MPE in one patient (4.5%) 14 days after the MCPF, which disappeared spontaneously after 24 hours. Conclusion The MCPF offers a real alternative in certain cases of pericardial effusion. We recommend this method especially for the definitive surgical palliation of MPE.